PROSPEK PROGRAM STUDI PERBANKAN SYARIAH - Muhammad Kamal Zubair (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2018)
Abstract: Along with the opening of Sharia Banking Courses at STAIN Parepare, there are some things that require an immediate answer problems, such as how the response of potential users graduates of the courses and how their appreciation of the opening of the courses as well as how their expectations for graduates of Sharia Banking Courses. This study aimed to obtain descriptive information about the responses and expectations of Islamic Financial Institutions in Parepare on the opening of the Sharia Banking Courses at STAIN Parepare as potential users of the graduates of Sharia Banking Courses. The results showed that the manager of Islamic Financial Institutions appreciation against the opening of Sharia Banking Courses very positive. Islamic banking and Islamic financial institutions in Parepare gave high appreciation to the opening of this course. The practitioners of Islamic financial institutions also hope Sharia Banking Courses graduates are able to master the concept of Islamic banking both in the realm of theory and practice. Abstrak: Seiring dengan pembukaan program studi Perbankan Syariah di STAIN Parepare, terdapat beberapa hal permasalahan yang memerlukan jawaban segera, diantaranya adalah bagaimanakah respon calon pengguna lulusan program studi tersebut dan bagaimanakah apresiasi mereka terhadap pembukaan Program Studi tersebut serta bagaimanakah harapan mereka terhadap lulusan Program Studi Perbankan Syariah. Penelitian ini bertujuan untuk memperoleh informasi deskriptif mengenai tanggapan dan harapan Lembaga Keuangan Syariah di Parepare terhadap pembukaan Program Studi Perbankan Syariah di STAIN Parepare sebagai calon pengguna lulusan program studi tersebut. Hasil penelitian menunjukkan bahwa sikap dan apresiasi pengelola Lembaga Keuangan Syariah terhadap pembukaan Program Studi Perbankan Syariah sangat positif sekali. Lembaga keuangan dan perbankan syariah yang ada di Parepare memberikan apresiasi yang tinggi terhadap pembukaan program studi ini. Para praktisi lembaga keuangan syariah juga berharap lulusan Program Studi Perbankan Syariah mampu menguasai konsep perbankan syariah baik pada ranah teori maupun praktek.